2014
DOI: 10.1128/mbio.01864-14
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Invasion in a Diverse Set of Fusobacterium Species

Abstract: The diverse Fusobacterium genus contains species implicated in multiple clinical pathologies, including periodontal disease, preterm birth, and colorectal cancer. The lack of genetic tools for manipulating these organisms leaves us with little understanding of the genes responsible for adherence to and invasion of host cells. Actively invading Fusobacterium species can enter host cells independently, whereas passively invading species need additional factors, such as compromise of mucosal integrity or coinfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 73 publications
6
81
0
Order By: Relevance
“…Invasion of endothelial cells by F. nucleatum in mouse placenta has been observed [51]. The invasiveness of F. nucleatum varies widely among different strains, and has been shown as directly related to the IBD disease status [77,97]. …”
Section: Virulence Mechanisms Of F Nucleatummentioning
confidence: 99%
“…Invasion of endothelial cells by F. nucleatum in mouse placenta has been observed [51]. The invasiveness of F. nucleatum varies widely among different strains, and has been shown as directly related to the IBD disease status [77,97]. …”
Section: Virulence Mechanisms Of F Nucleatummentioning
confidence: 99%
“…F. nucleatum has been found in higher levels in CRC, and adenomas, compared to adjacent normal tissue . It is a highly adhesive bacterial species and has the ability to invade colonic epithelial cells . Additionally, recent studies showed that, in human CRC, high amounts of F. nucleatum in tumor tissue is correlated to low infiltration of T lymphocytes and poor patient prognosis …”
mentioning
confidence: 99%
“…10,[23][24][25] It is a highly adhesive bacterial species and has the ability to invade colonic epithelial cells. 13,29 Additionally, recent studies showed that, in human CRC, high amounts of F. nucleatum in tumor tissue is correlated to low infiltration of T lymphocytes and poor patient prognosis. 30,31 In this study, we investigated the utility of microbial markers for clbA1 bacteria (clbA) and, afa-11 DAEC (afaC), and F. nucleatum, in CRC detection, using 238 human stool samples from the FECSU (the Faecal and Endoscopic Colorectal Study in Umeå) cohort.…”
mentioning
confidence: 99%
“…Despite the extensive phylogenetic analysis of Fusobacterium and our increasing understanding of what is required to be a virulent strain, our knowledge of the specific virulence mechanisms remains limited. For instance, it was previously shown that multiple F. necrophorum and F. mortiferum strains were significantly more invasive than F. nucleatum strains into keratinocytes, which is in direct conflict with bioinformatic reports that place these species in the non-invasive or passively invasive category (24,25) . F. necrophorum and F. mortiferum are invasive but have not been associated with colorectal cancer, which raises an additional question of how virulence is truly regulated in this disease.…”
Section: Introductionmentioning
confidence: 93%
“…In a recent study, Fusobacterium species were bioinformatically divided into actively invading species ( F. nucleatum , F. periodonticum , F. varium , F. ulcerans ) ( Fig. 1C ), passively invading species that are believed to need a compromised epithelial barrier for cellular entry ( F. necrophorum , F. gonidiaformans ), and those with unknown invasive potential ( F. mortiferum ) (24) . Despite the extensive phylogenetic analysis of Fusobacterium and our increasing understanding of what is required to be a virulent strain, our knowledge of the specific virulence mechanisms remains limited.…”
Section: Introductionmentioning
confidence: 99%